Emotion or Evaluation: Cultural Differences in the Parental Socialization of Moral Judgement - Senzaki, Sawa; Cowell, Jason M.; Shimizu, Yuki; Calma-Birling, Destany (Frontiers in Human Neuroscience, 2022)
Moral reasoning develops rapidly in early childhood. Recent evidence from cognitive neuroscience literature suggests that the development of moral reasoning is supported by an integration of cognitive and affective components. However, the role of culture in the development of moral reasoning in young children is under-investigated. Previous cross-cultural research suggests that culture shapes how people interpret other’s behaviors. In particular, people raised in independent cultures, such as the U.S., tend to form impressions of others and attribute others’ behaviors to their personal dispositions more quickly than people raised in interdependent cultures, such as Japan. In the present cross-cultural study, we examined parents’ discourse with children in Japan and the U.S. Parents and their 3- to 4-year-old children were asked to view and discuss cartoon characters depicting prosocial and antisocial acts. Results indicated that in both cultures, parents discussed about moral actions (e.g., helping, harming) of characters. Furthermore, US parents were more likely to evaluate dispositional characteristics of characters based on their pro-social and ant-social acts, whereas Japanese parents were more likely to refer to emotion of the characters who got hurt. We discuss implications of cross-cultural differences and similarities in parental moral socialization and the development of moral reasoning in young children.